2019
DOI: 10.21601/ortadogutipdergisi.604271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brain Death in Children: A Single Center Experience

Abstract: Introduction: Brain death is defined as a status of apnea, coma and the absence of brainstem reflexes, in addition to the presence of electrocerebral silence (ECS) on an electroencephalography (EEG). Trauma and anoxic encephalopathy are the most common causes of brain death in children, with incidences of brain death reported to vary between 0.65-1.2 percent. A diagnosis of brain death can be made based on a detailed anamnesis, physical examination findings and supportive test results. When pediatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…They also revealed that the combination of EEG and AT was the most used ancillary method, in about 65% of their study cohort, like the observation in our study. 14 Aslan et al 18 from Turkey reported similarly high rates of ancillary tests in their study group, including 20 pediatric BD cases. In their report, they showed that they routinely use EEG and AT in 19 out of 20 patients, whereas CTA/MRA was applied to 8 patients (40%).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…They also revealed that the combination of EEG and AT was the most used ancillary method, in about 65% of their study cohort, like the observation in our study. 14 Aslan et al 18 from Turkey reported similarly high rates of ancillary tests in their study group, including 20 pediatric BD cases. In their report, they showed that they routinely use EEG and AT in 19 out of 20 patients, whereas CTA/MRA was applied to 8 patients (40%).…”
Section: Discussionmentioning
confidence: 76%
“…Sari et al 23 reported that the time to BD in their study group was in a range between 1 and 21 days, with a median of 3 days. 23 Aslan et al 18 reported a wider interval, with a range between 2 and 33 days and a mean of 11.1 days. 18 Özmert et al 21 reported that the time from BD declaration to cardiac arrest was a mean 6.9 days (0.2-25 days).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations